Realidad actual y funcionamiento de las bibliotecas públicas municipales : estudio realizado a los municipios de guayabal de Síquima, Bituima, Vianí, y San Juan de Rioseco de la región del Magdalena centro - Obregón Galindo, Adriana Isabel (Universidad de La Salle. Facultad de Ciencias Económicas y Sociales. Sistemas de Información, Bibliotecología y Archivística., 2017)
This research makes a demonstrative work from a field in municipal libraries in order to establish the status of these institutions, from the perspective of their role in small communities with limited development of these resources. Proposes a methodology based on interviews with those responsible for libraries and from the results, it proposes a series of recommendations to continue to improve service and achieve greater impact on communities affecting such establishments. Keywords: Library, public libraries, institutions, culture, cultural, social, methodology.